MINGLING PROCESSES IN THE EARTH'S CRUST: GEOLOGICAL OBSERVATIONS AND MATHEMATICAL SIMULATION - A. G. Vladimirov; V. G. Vladimirov; O. P. Polyansky (Геодинамика и тектонофизика, 2017)
This issue of Geodynamics & Tectonophysics presents the state-of-the-art studies of mingling processes and investigations of the interactions between the mafic and acidic melts of contrasting compositions at various depths of the Earth's crust. The diagnostic features and the genesis of magmatic and synmetamorphic mingling are discussed with respect to the reference objects of Altaides and Uralides. Several papers report on the results of mathematical simulation used to discover the mechanism for lifting the high-density basite inclusions in a chamber or a dyke filled with salic magma. This special issue is intended for researchers and specialists in geology, petrology and geodynamics of magmatic processes in the crust, as well as for lecturers, post-graduate students and university students.